2004
DOI: 10.1073/pnas.0305799101
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of oxidative stress-induced abnormalities in ceramide and cholesterol metabolism in brain aging and Alzheimer's disease

Abstract: Alzheimer's disease (AD) is an age-related disorder characterized by deposition of amyloid ␤-peptide (A␤) and degeneration of neurons in brain regions such as the hippocampus, resulting in progressive cognitive dysfunction. The pathogenesis of AD is tightly linked to A␤ deposition and oxidative stress, but it remains unclear as to how these factors result in neuronal dysfunction and death. We report alterations in sphingolipid and cholesterol metabolism during normal brain aging and in the brains of AD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

38
872
2
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,012 publications
(920 citation statements)
references
References 51 publications
38
872
2
8
Order By: Relevance
“…SPHs are precursors for ceramide production. Their accumulation induces apoptosis and seems to worsen neurodegeneration by increasing Aβ biosynthesis and promoting gamma-secretase processing of APP (Cutler et al, 2004;Grimm et al, 2005;Puglielli et al, 2003). Our findings closely resemble other work showing that global brain levels of ceremides, sphingolipids and related molecules are increased in the cerebral cortex of APP SL /PS1Ki and APP/PS1 mice especially after the age of 6 months (Barrier et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…SPHs are precursors for ceramide production. Their accumulation induces apoptosis and seems to worsen neurodegeneration by increasing Aβ biosynthesis and promoting gamma-secretase processing of APP (Cutler et al, 2004;Grimm et al, 2005;Puglielli et al, 2003). Our findings closely resemble other work showing that global brain levels of ceremides, sphingolipids and related molecules are increased in the cerebral cortex of APP SL /PS1Ki and APP/PS1 mice especially after the age of 6 months (Barrier et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Aging results in the accumulation of various stress factors, including pro-inflammatory and oxidative stress molecules that can stimulate sphingomyelinase activities, leading to the production of the pro-apoptotic lipid, ceramide (Cutler et al, 2004;Joseph et al, 2000). Alzheimer's disease is the most common form of age-related dementia, characterized by the accumulation of Aβ peptides in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Ceramide is an important second messenger molecule that regulates diverse cellular processes including cell growth, differentiation, and apoptosis. Ceramide levels also increase in response to aging and various age-related stress factors (e.g., oxidative stress), and are directly involved in apoptotic signaling in various cell types, including neurons (Costantini et al, 2005;Cutler et al, 2004;Kolesnick and Kronke, 1998;Perez et al, 2005). Furthermore, ceramide stabilizes the APP cleaving enzyme 1 (BACE1), promoting Aβ biogenesis (Patil et al, 2007;Puglielli et al, 2003), and reduction of ceramide levels leads to reduced secretion of APP and Aβ in human neuroblastoma cells (Tamboli et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,58 Lipid droplets are currently considered to be metabolically active organelles, and their behavior in stressed cells is intriguing, as lipid metabolism is impaired during oxidative stress. 59,60 Only very limited information is available for communications between lysosomes and LD. Liu et al identified proteins that are common between LD and lysosomes, such as Rab7 and SNAP, suggesting a possible link between these organelles.…”
Section: Discussionmentioning
confidence: 99%